2013
DOI: 10.1002/ijc.28658
|View full text |Cite
|
Sign up to set email alerts
|

Methylomics analysis identifies epigenetically silenced genes and implies an activation of β‐catenin signaling in cervical cancer

Abstract: Using DNA methylation biomarkers in cancer detection is a potential direction in clinical testing. Some methylated genes have been proposed for cervical cancer detection; however, more reliable methylation markers are needed. To identify new hypermethylated genes in the discovery phase, we compared the methylome between a pool of DNA from normal cervical epithelium (n 5 19) and a pool of DNA from cervical cancer tissues (n 5 38) using a methylation bead array. We integrated the differentially methylated genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 51 publications
1
58
0
Order By: Relevance
“…It interacts with E-cadherin–β-catenin complexes in polarized epithelial cells. The methylation of AJAP1 may lead to the release of β-catenin and the activation of Wnt signaling [22]. AJAP1 expression has been recently reported to be reduced in HCC compared with non-cancerous liver tissues and to be associated with hypermethylation of the AJAP1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…It interacts with E-cadherin–β-catenin complexes in polarized epithelial cells. The methylation of AJAP1 may lead to the release of β-catenin and the activation of Wnt signaling [22]. AJAP1 expression has been recently reported to be reduced in HCC compared with non-cancerous liver tissues and to be associated with hypermethylation of the AJAP1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…More recent deep sequencing studies have found translocations involving MAGI-2 and PTEN in human prostate tumors (21), and genetic deletion and rearrangement of MAGI-2 in a human melanoma cell line (22). MAGI-2 has also been identified as a target of miRNAs that are upregulated in tumors (23,24), and is hypermethylated in cervical cancer tissue (25).…”
Section: Magi-2/s-scam | Glomerulosclerosismentioning
confidence: 99%
“…In this context, glioma cells stably overexpressing AJAP1 show a reduced migratory capacity compared to wild-type cells suggesting that AJAP1 actually has an inhibiting effect on cell migration (McDonald et al, 2006). Overexpression of AJAP1 in oligodendroglioma cell lines indicates that AJAP1 localizes at the adherens junctions, where it could interact with β-catenin (Chen et al, 2014; Zeng et al, 2014). In surgical sections of diffuse astrocytoma, AJAP1 localizes at the cell membrane, whereas in oligodendroglioma sections AJAP1 is not detectable at all (Zeng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%